Ensino de espanhol para brasileiros : das crenças à prática docente - Vieira, Dark dos Santos (Universidade Federal de São Carlos, 2012)
In recent years, we have observed that the presence of the Spanish language teaching in regular schools has been expanded gradually. However, even in the context of teaching-learning favoring of the Spanish language, it is quite frequently to hear from professionals in other fields and language learners that the broad similarity between Portuguese and Spanish facilitates communication among speakers of the two languages, and for that reason, Portuguese speakers would not need to devote themselves so deeply and systematically to the study of Spanish (or vice versa). In the field of Applied Linguistics around the same period, the number of researches focusing on beliefs related to the teaching-learning language process have increased and the results indicate the need for knowledge of teacher beliefs (trainers and training) so that one could achieve critical-reflexive education. From these findings, this ethnographic-based research developed under an interpretative perspective aims to investigate the perceptions and beliefs of Spanish teachers on the teaching of this language for Brazilians, and see how the relationship of the beliefs of these teachers with their context and their practice in the classroom is characterized. The participants of this survey were teachers of Spanish for Brazilians students in the metropolitan region of Campinas, São Paulo, and as instruments for data collection, we used a mixed questionnaire (with open questions and items in scale), interviews with teachers, field notes and recordings lessons in audio and video. This study took place on the basis of discussions on approaches to Teaching, teaching-learning language and beliefs. The data show us that, in general, the practice of teachers is guided by a system of beliefs and assumptions that underlie their approach to teaching. In addition, we also note that both beliefs about the approach of teaching have a strong relationship with the teaching context.

En los últimos años, se observó que la presencia de la enseñanza de la Lengua Española en las escuelas regulares se ha ampliado gradualmente en Brasil. Sin embargo, incluso en este contexto de favorecimiento de aprendizaje de ese idioma extranjero, es bastante frecuente oír de profesionales de otros campos y estudiantes de idiomas, que la gran similitud entre el portugués y el español facilita la comunicación entre los hablantes de las dos lenguas y que por lo tanto no sería necesario un hablante de portugués dedicarse a estudiar con ahínco y sistemática el español (o viceversa). En el campo de la Lingüística Aplicada en el mismo período, se ha incrementado el número de investigaciones que se centran en las creencias relacionadas con el proceso de enseñanza-aprendizaje de idiomas, los resultados indican la necesidad de que el conocimiento de las creencias de profesores (formadores y en formación) es necesario para que se pueda lograr una educación crítico-reflexiva. A partir de estos hallazgos, esta investigación de base etnográfica, desarrollado bajo una perspectiva interpretativa, tiene el objetivo de investigar las percepciones y creencias de los profesores de español en la enseñanza de este idioma en Brasil y verificar cómo se caracteriza la relación de las creencias de estos maestros con su contexto y su práctica en el aula. Los participantes de la investigación fueron profesores de español para brasileños en la región metropolitana de Campinas, São Paulo y como instrumentos para la recolección de datos se utilizaron un cuestionario mixto (con preguntas abiertas y respuestas en escala), entrevistas con profesores, notas de campo y grabaciones de lecciones en audio y video. Este estudio se llevó a cabo sobre la base de los debates sobre los enfoques para la enseñanza, la enseñanza-aprendizaje de lenguas y creencias. Los datos nos muestran que, en general, la práctica de los profesores es guiado por un sistema de creencias y supuestos que subyacen su enfoque de enseñanza. Además, se verificó también, que ambas, creencias y enfoque de enseñanza, tienen una fuerte relación con el contexto de enseñanza.
Keywords: Ensino de espanhol; Crenças; Abordagem de ensinar; Spanish teaching; Beliefs; Teaching approach; Enseñanza de español; Creencias; Enfoque de enseñanza; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA